2016
DOI: 10.1093/mnras/stw1987
|View full text |Cite
|
Sign up to set email alerts
|

Orbital alignment and star-spot properties in the WASP-52 planetary system

Abstract: We report 13 high-precision light curves of eight transits of the exoplanet WASP-52 b, obtained by using four medium-class telescopes, through different filters, and adopting the defocussing technique. One transit was recorded simultaneously from two different observatories and another one from the same site but with two different instruments, including a multi-band camera. Anomalies were clearly detected in five light curves and modelled as star-spots occulted by the planet during the transit events. We fitte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
69
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(77 citation statements)
references
References 57 publications
(86 reference statements)
7
69
1
Order By: Relevance
“…The resulting transit parameters agree well with previous studies (Hébrard et al 2013;Kirk et al 2016;Mancini et al 2017), except for R p /R , which appears shallower than previously reported. This deviation is probably caused by stellar activity, given that occulted star spots (Mancini et al 2017) and faculae (Kirk et al 2016) have been identified several times.…”
Section: Light-curve Analysissupporting
confidence: 91%
See 3 more Smart Citations
“…The resulting transit parameters agree well with previous studies (Hébrard et al 2013;Kirk et al 2016;Mancini et al 2017), except for R p /R , which appears shallower than previously reported. This deviation is probably caused by stellar activity, given that occulted star spots (Mancini et al 2017) and faculae (Kirk et al 2016) have been identified several times.…”
Section: Light-curve Analysissupporting
confidence: 91%
“…2, the derived GTC/OSIRIS transmission spectrum for WASP-52b does not exhibit any broad spectral signatures, except for the narrow excess absorption at the Na line. The standard deviation of the 16.5 nm transit depths σ(R p /R ) = 0.00110 is smaller than one atmospheric scale height H/R = kT/(µgR ) = 0.00126, where the stellar radius R = 0.786 R , the planetary surface gravity g = 6.85 m s −2 and the planetary equilibrium temperature T eq = 1315 K were taken from Mancini et al (2017); k is the Boltzmann constant; µ is the mean molecular weight (MMW) and assumed as 2.3× proton mass.…”
Section: Transmission Spectrummentioning
confidence: 99%
See 2 more Smart Citations
“…More information about these telescopes and instruments is available in previous papers (e.g. Mancini et al 2018). The same transit was also observed with the Danish telescope using a Bessell-U filter, in order to have a wavelength coverage in the near-ultraviolet as well.…”
Section: Photometrymentioning
confidence: 87%